INFILTRATION METASOMATISM AT LHERZ AS MONITORED BY SYSTEMATIC ION-MICROPROBE INVESTIGATIONS CLOSE TO A HORNBLENDITE VEIN - Zanetti A.; Vannucci R.; Bottazzi P.; Oberti R.; Ottolini L. (My University, 1996)
Systematic investigations (electron- and ion-microprobe, and X-ray structure-refinement) of pyroxenes and amphiboles close to a cm-wide hornblendite vein have been carried out on a composite peridotite sample from the Lherz massif with the aim of constraining the processes of melt infiltration in the subcontinental mantle.Vein amphiboles have light rare earth element (LREE)-enriched patterns with the maximum at Nd and Sm, and positive Ba, Nb, Sr, and Ti anomalies. The liquid flowing in the vein had an alkaline geochemical signature (i.e., large-ion lithophile element (LILE)-enriched without significant high field strength element (HFSE) anomalies). Modal metasomatism, represented by crystallization of amphibole and consumption of clinopyroxene, occurred in a 2-cm thick layer of wall-rock. Newly formed amphiboles, i.e., those in the vein and in the modally metasomatised layer, have a lower Al disorder than the pre-existing disseminated amphiboles, which formed during an older metasomatic event.Cryptic metasomatism is recorded beyond the modally altered layer in the cores of clinopyroxenes and in amphiboles. Moving away from the vein towards the peridotite, amphiboles and pyroxenes display systematic compositional variations, and approach equilibrium with the wall-rock within a few cm. Porphyroclastic clinopyroxenes record chromatographic separation of elements: less incompatible elements reach equilibrium with the wall-rock lherzolite at shorter distances than the more incompatible ones. The inverse correlation between the depth of the metasomatic effect and partition coefficients in porphyroclastic clinopyroxenes indicates that different concentration fronts developed for different elements during liquid/rock interaction, suggesting that liquid percolation along grain boundaries was responsible for clinopyroxene metasomatism.As in the clinopyroxene, abundances of incompatible elements in the amphibole decrease in the peridotite with distance from the vein. However, a less marked separation of elements is recorded by the amphiboles. Elements that are markedly more compatible in amphibole than in other minerals of a lherzolite, such as K, Ba, and Rb, have abrupt gradients which are confined to the modally-metasomatised region. The lack of metasomatic enrichment in these elements in the farther, disseminated amphiboles, indicates that amphibole crystallization was synchronous with melt infiltration and acted as a buffer for such elements.Micro-analytical investigations indicate that the geochemical effects associated with small-scale liquid infiltration can be successfully described by models which take into account both the chromatographic fractionation of elements and the influence of mineral-assemblage variations.
Keywords: LHERZOLITE; HORNBLENDITE VEIN; INFILTRATION METASOMATISM; TRACE ELEMENTS; ION MICROPROBE